Differential Effects of p38, MAPK, PI3K or Rho Kinase Inhibitors on Bacterial Phagocytosis and Efferocytosis by Macrophages in COPD. - Martin A Bewley; Kylie B R Belchamber; Kirandeep K Chana; Richard C Budd; Gavin Donaldson; Jadwiga A Wedzicha; Christopher E Brightling; Iain Kilty; Louise E Donnelly; Peter J Barnes; Dave Singh; Moira K B Whyte; et al. (PLoS ONE)
Pulmonary inflammation and bacterial colonization are central to the pathogenesis of chronic obstructive pulmonary disease (COPD). Defects in macrophage phagocytosis of both bacteria and apoptotic cells contribute to the COPD phenotype. Small molecule inhibitors with anti-inflammatory activity against p38 mitogen activated protein kinases (MAPKs), phosphatidyl-inositol-3 kinase (PI3K) and Rho kinase (ROCK) are being investigated as novel therapeutics in COPD. Concerns exist, however, about off-target effects. We investigated the effect of p38 MAPK inhibitors (VX745 and SCIO469), specific inhibitors of PI3K α (NVS-P13K-2), δ (NVS-P13K-3) or γ (NVS-P13K-5) and a ROCK inhibitor PF4950834 on macrophage phagocytosis, early intracellular killing of bacteria and efferocytosis of apoptotic neutrophils. Alveolar macrophages (AM) obtained from broncho-alveolar lavage (BAL) or monocyte-derived macrophages (MDM) from COPD patients (GOLD stage II/III) enrolled from a well characterized clinical cohort (MRC COPD-MAP consortium) or from healthy ex-smoker controls were studied. Both COPD AM and MDM exhibited lower levels of bacterial phagocytosis (using Streptococcus pneumoniae and non-typeable Haemophilus influenzae) and efferocytosis than healthy controls. None of the inhibitors altered bacterial internalization or early intracellular bacterial killing in AM or MDM. Conversely PF4950834, but not other inhibitors, enhanced efferocytosis in COPD AM and MDM. These results suggest none of these inhibitors are likely to exacerbate phagocytosis-related defects in COPD, while confirming ROCK inhibitors can enhance efferocytosis in COPD.